Assessment of determinant factors of pregnancy termination among women of reproductive age group in Ethiopia: Evidence from 2016 Ethiopian Demographic and Health Survey - Berhanu Teshome Woldeamanuel (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2019)
Background: Pregnancy termination is a major public health globally in the highly important for maternal mortality. In this study, we have assessed cross-sectional data from Ethiopian Demographic and Health Survey to identify the occurrence of pregnancy termination and its risk factors from various women socioeconomic and demographic and characteristics. Methods: The information collected from 15,683 women of the reproductive age group was considered in the study, and variables like maternal social and demographic characteristics were considered as risk factors of pregnancy termination. The study used descriptive statistics and binary logistic regression model to identify signifi cant risk factors attributed to pregnancy termination.